Respuesta :
Answer:
The solution is the point (3,5)
The graph in the attached figure
Step-by-step explanation:
step 1
Line A ----> (2,6),(6,2)
Find the equation of the line A
Find the slope
m=(2-6)/(6-2)
m=-1
Find the equation of the line into point slope form
The equation is equal to
y-y1=m(x-x1)
we have
m=-1
point (2,6)
substitute
y-6=-1(x-2)
y=-x+2+6
y=-x+8 ------> equation of the line A
step 2
Line B ----> (0,3),(4.5,6)
Find the equation of the line B
Find the slope
m=(6-3)/(4.5-0)
m=(2/3)
Find the equation of the line into point slope form
The equation is equal to
y-y1=m(x-x1)
we have
m=(2/3)
point (0,3)
substitute
y-3=(2/3)(x-0)
y=(2/3)x+3 ------> equation of the line B
step 3
Solve the system of equations by graphing
Remember that the solution of the system of equations is the intersection point both lines
The solution is the point (3,5)
see the attached figure
![Ver imagen calculista](https://us-static.z-dn.net/files/df3/247f104650c4a3400362c3581c26a454.jpg)